2005
DOI: 10.2460/javma.2005.226.1881
|View full text |Cite
|
Sign up to set email alerts
|

Changes over time in echocardiographic measurements in young Standardbred racehorses undergoing training and racing and association with racing performance

Abstract: Results suggest that age must be taken into account when interpreting results of echocardiography in young Standardbred racehorses because significant cardiac enlargement takes place with age and training. A larger heart was found in horses that were racing, and size of the heart was correlated with athletic performance of the horse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 32 publications
10
86
3
5
Order By: Relevance
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 49%
“…Seder et al [26] observed that age-and weightadjusted means for cardiac dimensions were lower in males Thoroughbreds than in females aged between 12 and 27 months. Buhl et al [5] in young Standardbred racehorses reported larger LVID in males. In the Spanish foals of our research, in main lines, the fillies had higher LVIDd, but lower LVIDs, LVFWTs, EPSS and LVM.…”
Section: Comparisons Of Echocardiographic Measurements Between Spanismentioning
confidence: 86%
See 1 more Smart Citation
“…Körperliches Training hat eine Auswirkung auf die Herzgröße und die Herzfunktion (Young 1999, Buhl et al 2005, Young et al 2005, Sleeper et al 2014. Pferde zeigen dabei ähnli-che trainingsinduzierte Anpassungen des Herzens wie der Mensch, wobei diese Anpassungen beim Pferd jedoch meistens etwas geringer ausgeprägt sind (Harmeyer 2005).…”
Section: Introductionunclassified
“…Sendo que, o conhecimento da anatomia ecocardiográfica normal representa a base para identificação e interpretação dos achados anormais. A mensuração da dimensão cardíaca foi considerada a mais importante ao se avaliar severidade e prognóstico de doenças cardíacas, assim como a resposta ao treinamento (Buhl et al 2005, Zucca et al 2008.…”
Section: Introductionunclassified